A response to William Beinart and Peter Delius' Rejoinder. Issue 1 (2nd January 2021) - Cousins, Ben
ABSTRACT: The rejoinder by Beinart and Delius sheds further light on the convergence and divergence of our views on land tenure reform in contemporary South Africa. Convergence on such issues as the need for policies to offer a range of options and choices in relation to land tenure systems is briefly noted. Divergence is most notable in relation to contrasting assessments of the option of democratized versions of social tenure, in which shared rights are vested in individuals and families rather than institutions. Other disagreements exist in relation to the interpretation of processes of historical change, and the need for land rights that can underpin both accumulation and social reproduction.